KOMUNIKASI DAKWAH GUS IQDAM BERBASIS NILAI-NILAI ISLAM DAN BUDAYA JAWA PADA PLATFORM DIGITAL YOUTUBE - Iswahyu Pranawukir; Tia Nurapriyanti; Zulham, Zulham; Rety Palupi; Yanti Setianti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
This consider looks at the dakwah (Islamic lecturing) communication procedures utilized by Gus Iqdam on the advanced stage YouTube, centering on the integration of Islamic values and Javanese culture. As a minister, Gus Iqdam utilizes YouTube to provide devout messages with a interesting approach, combining Islamic lessons with Javanese nearby shrewdness. The objective of this think about is to get it how Gus Iqdam bundles and passes on his dakwah to stay pertinent and locks in to a different group of onlookers. The investigate strategy utilized is substance examination of Gus Iqdam's dakwah recordings on YouTube, in conjunction with interviews with a few of his devotees. The comes about demonstrate that Gus Iqdam effectively creates an successful dakwah communication demonstrate through the utilize of effectively reasonable dialect, neighborhood stories, and solid Javanese social images. This approach not as it were improves gathering of people understanding and engagement but too improves the dakwah with important and important nearby social legacy. These discoveries recommend that the integration of neighborhood social values in computerized dakwah can be an successful methodology in passing on devout messages that are more relevant and effectively acknowledged by the broader community.